Control of competing hydrogenation of phenylhydroxylamine to aniline in a single-step hydrogenation of nitrobenzene to p-aminophenol - Nadgeri, Jayprakash M.; Biradar, Narayan S.; Patil, Priyanka B.; Jadkar, Sachin T.; Garade, Ajit C.; Rode, Chandrashekhar V. (Industrial & Engineering Chemistry Research, 2011)
Two steps involving catalytic hydrogenation of nitrobenzene to phenylhydroxylamine (PHA) in acid medium and its rearrangement to p-aminophenol (PAP) were studied separately in a batch reactor, using a well-characterized 3% Pt/C catalyst. The first step of hydrogenation of nitrobenzene to PHA could be carried out at 303 K and a H(2) pressure of 0.69 MPa with complete conversion of nitrobenzene, while the achieved selectivity to PHA was higher than 90% with some formation of aniline, even at lower temperature. The second step of PHA rearrangement to PAP could be achieved under a hydrogen atmosphere at elevated temperature of 353 K to give a maximum selectivity to PAP of 74%.